Global prevalence and antibiotic resistance profiles of carbapenem-resistant Pseudomonas aeruginosa reported from 2014 to 2024: a systematic review and meta-analysis - Ramatla, Tsepo; Nkhebenyane, Jane; Lekota, Kgaugelo E.; Thekisoe, Oriel; Monyama, Maropeng; Achilonu, Conrad Chibunna; Khasapane, George (Frontiers in Microbiology, 2025)
IntroductionCarbapenem-resistant Pseudomonas aeruginosa (CRPA) represents a global threat, but the global distribution of carbapenem resistant bacteria remains a critical issue in public health.MethodsWe conducted a systematic review and meta-analysis on the global pooled prevalence estimate (PPE) of CRPA and their antibiotic resistance. The systematic review protocol was registered with PROSPERO (CRD42024579654). This study was carried out following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Heterogeneity between studies was assessed using Cochrane Q test and I2 test statistics based on the random effects model. Comprehensive meta-analysis software v4.0 was used to analyze the pooled prevalence of CRPA.ResultsA total of 163 studies (both clinical and screening samples) containing a total of 58,344 cases from 39 countries were included in this study. The overall PPE of CRPA was 34.7% (95% CI: 0.316–0.37.8) for both clinical and screening samples. Meropenem had a PPE of 31.2% (95% CI: 0.272–0.352) and imipenem had the lowest PPE of 27.7% (95% CI: 0.238–0.319). Japan had the highest PPE at 98.2% (95% CI: 0.482–0.100) of CRPA, and the lowest was observed for Saudi Arabia at 13.9% (95% CI: 0. 064–0. 277). CRPA is widespread on five continents except Australia and Antarctica, while the highest PPE is in Europe at 47.6% (95% CI: 0.359–0.595) and the lowest in Asia at 32, 8% (95% CI: 0.293–0.364). The relatively higher PPE of CRPA was observed in Europe during the year interval 2014–2017 at 95.4% (95% CI: 0.388–0.999), followed by Africa from the year 2022–2024 with 38.5% (95% CI: 0.243–0.550). Ceftazidime was significantly higher in studies conducted before 2019 with a PPE of 44.7% (95% CI: 0.246% – 0.668), while CRPA after 2019 had a higher resistance to cefoperazone/sulbactam with a PPE of 17.3% (95% CI: 0.050–0.455).DiscussionThis review indicates that the prevalence of CRPA is generally high and varies significantly between countries. To prevent the emergence of CRPA and antibiotic resistance, future initiatives should prioritise strengthening laboratory capacity for early detection of antibiotic resistance.